Novel Bionic Topography with MiR-21 Coating for Improving Bone-Implant Integration through Regulating Cell Adhesion and Angiogenesis - Geng, Zhen; Li, Zhaoyang; Cui, Zhenduo; Wang, Jing; Yang, Xianjin; Liu, Changsheng (Nano letters, 2020)
Implant loosening is still the major form of the failure of artificial joints. Herein, inspired by the operculum of the river snail, we prepared a novel bionic micro/nanoscale topography on a titanium surface. This bionic topography promoted early cell adhesion through up-regulating the expression of ITG α5β1 and thus accelerated the following cell spreading, proliferation, and differentiation. Moreover, a miR-21 coating, which promoted the angiogenic differentiation of MSCs, was fabricated on the bionic topography. Benefiting from both bionic micro/nanoscale topography and miR-21, blood vessel growth and bone formation and mineralization around the implant, as well as bone-implant bonding strength, were significantly improved. Collectively, the present study highlights the combination of the bionic micro/nanoscale topography and miR-21 on promoting cell adhesion and angiogenic differentiation and improving in vivo angiogenesis and bone-implant osseointegration. This work provides a new train of thought propelling the development of implants for potential application in the orthopedics field.